Diurnal patterns of methane emissions from paddy rice fields in the Philippines - Weller, Sebastian; Kraus, David; Butterbach-Bahl, Klaus; Wassmann, Reiner; Tirol-Padre, Agnes; Kiese, Ralf (Wiley, 2015)
Methane (CH4) emissions from rice paddies often show significant diurnal variations, most likely driven by diurnal changes of radiation and temperature in air, floodwater, and soil. Field measurements, however, are often scheduled at a fixed time of a given measuring day, thereby neglecting sub‐daily variations of CH4 emissions. Here we evaluated diurnal patterns of CH4 emissions from traditional paddy rice production as observed during field measurements in the Philippines. Field emissions were measured during three consecutive cropping seasons using an automated chamber and gas sampling system with fluxes being obtained every 4 h. Methane fluxes were monitored with a total of nine chambers during the dry seasons in 2012 and 2013 and 27 chambers during the wet season in 2012. Significant and consistent diurnal patterns of CH4 emissions were mainly observed from the start of field flooding until the middle of cropping periods, i.e., periods with low leaf area of the rice crop. Our data show that disregarding the diurnal variability of fluxes results in an average overestimation of seasonal CH4 emissions of 22% (16–31%) if measurements were conducted only around noon. Scheduling manual sampling either at early morning (7:00–9:00) or evening (17:00–19:00) results in estimations of seasonal emissions within 94–101% of the “true” value as calculated from multiple daily flux measurements. Alternatively, uncertainties of seasonal emissions can be reduced to an average of ≤3% by applying sinus function or Gauss function‐based correction factors. Application of correction factors allows the performance of flux measurements at any time of day. We also investigated N2O emissions from rice paddies with respect to diurnal variations, but did not find, as in the case of CH4, any significant and persistent diurnal pattern.